2014
DOI: 10.1261/rna.045773.114
|View full text |Cite
|
Sign up to set email alerts
|

Rejection of tmRNA·SmpB after GTP hydrolysis by EF-Tu on ribosomes stalled on intact mRNA

Abstract: Messenger RNAs lacking a stop codon trap ribosomes at their 3 ′ ends, depleting the pool of ribosomes available for protein synthesis. In bacteria, a remarkable quality control system rescues and recycles stalled ribosomes in a process known as transtranslation. Acting as a tRNA, transfer-messenger RNA (tmRNA) is aminoacylated, delivered by EF-Tu to the ribosomal A site, and accepts the nascent polypeptide. Translation then resumes on a reading frame within tmRNA, encoding a short peptide tag that targets the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…We used two kinds of mRNAs having 0 and 21 nucleotides extending from the P-site in consideration of the span of the downstream mRNA path from the P-site (Figure 5A ). Ribosome was incubated with tRNA fMet and an mRNA having a Shine-Dalgarno (SD) sequence, an AUG start codon and 0 or 21 nucleotides of 3′ extension (mRNA + 0 or mRNA + 21) to produce a stalled ribosome as previously reported ( 17 ). This stalled ribosome was incubated with 5-TAMRA-labeled ArfA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used two kinds of mRNAs having 0 and 21 nucleotides extending from the P-site in consideration of the span of the downstream mRNA path from the P-site (Figure 5A ). Ribosome was incubated with tRNA fMet and an mRNA having a Shine-Dalgarno (SD) sequence, an AUG start codon and 0 or 21 nucleotides of 3′ extension (mRNA + 0 or mRNA + 21) to produce a stalled ribosome as previously reported ( 17 ). This stalled ribosome was incubated with 5-TAMRA-labeled ArfA.…”
Section: Resultsmentioning
confidence: 99%
“…Note that ArfA binds to the ribosome regardless of the length of 3′ extension of mRNA (Figure 5A ). Recently, we found that tmRNA-SmpB enters the ribosome stalled even in the middle of mRNA to trigger GTP hydrolysis by EF-Tu, whereas subsequent peptidyl-transfer occurs only in the ribosome stalled near the 3′ end of a truncated mRNA ( 17 ). Taken together, either ArfA or SmpB initially binds to the region around the decoding center for which the C-terminal region would not compete with the 3′ extension of mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of ribosome rescue in E. coli, the specific role of ArfB remains unclear, as ArfB has the same preference for ribosomes stalled on short mRNAs as tmRNA-SmpB and ArfA [11][12][13] . As suggested earlier, ArfB may be simply not as crucial in E. coli as in other species that lack one or both of the other rescue systems 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions in E. coli, ArfB appears redundant with tmRNA-SmpB and ArfA 6 . While tmRNA-SmpB and ArfA preferentially target ribosomes stalled on truncated mRNAs [11][12][13] , ArfB has been suggested to act on ribosomes stalled on mRNAs extending downstream past the P site 7,14 . If so, one potential function of ArfB could be to rescue ribosomes pausing on rare codon clusters 7 .…”
mentioning
confidence: 99%
“…However, the alternative pathways have evolved to compensate for the deficiency of trans-translation. For example, the alternative rescue factor A (ArfA) acts to release the stocked mRNA in Proteobacteria and mycobacteria, and the alternative rescue factor B (ArfB) appears in 34% of bacteria (Kurita et al, 2014; Huter et al, 2017; Fiedler et al, 2018). Therefore, superbacteria might have alternate ways for SmpB defects, while no reports indicate that other functions of SmpB are maintained by small RNA (sRNA).…”
Section: Introductionmentioning
confidence: 99%